The Evolving Landscape: Funerals, Cemeteries, Memorialization, and Bereavement Support. (December 2021) - Rumbold, Bruce; Lowe, Jennifer; Aoun, Samar M.
The aim of this study was to provide a better understanding of current memorialization practices and their influence on grief due to bereavement and to explore ways of improving bereavement outcomes. The qualitative research design incorporated two phases, a scoping literature review, followed by in-depth interviews with eight service providers from the funeral, cemetery, and crematorium industries across Australia. The trend toward informal memorialization practices blurs the roles of community members and formal industry service providers. A public health approach to bereavement support that encompasses both groups is recommended as the most appropriate response to the evolving landscape. This approach focuses on building partnerships between industry service providers and other community organizations involved in end-of-life issues. We propose that reframing the role of formal industry service providers as educators and facilitators partnered within compassionate communities will support improved outcomes for the bereaved.